2009
DOI: 10.1007/s12080-009-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence and the economic efficacy of marine reserves

Abstract: Predictions on the efficacy of marine reserves for benefiting fisheries differ in large part due to considerations of models of either intra-or inter-cohort population density regulating fish recruitment. Here, I consider both processes acting on recruitment and show using a bioeconomic model how for many fisheries density dependent recruitment dynamics interact with harvest costs to influence fishery profit with reserves. Reserves consolidate fishing effort, favoring fisheries that can profitably harvest low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 82 publications
2
17
0
Order By: Relevance
“…By contrast, when density dependence is strong the increase in larval supply resulting from spatially targeted reductions in fishing has little effect on recruitment in fished locations, so spatial management has little potential for increasing profits. This result is consistent with previous theoretical work that has shown that postsettlement density dependence makes MPAs less effective (23). A high cost of fishing also reduces the utility of spatial management.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, when density dependence is strong the increase in larval supply resulting from spatially targeted reductions in fishing has little effect on recruitment in fished locations, so spatial management has little potential for increasing profits. This result is consistent with previous theoretical work that has shown that postsettlement density dependence makes MPAs less effective (23). A high cost of fishing also reduces the utility of spatial management.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have identified scenarios in which reserves could be essential for maintaining high yields in spite of otherwise effective management regulations. These include, for example, the potentially critical function of reserves as a buffer against environmental stochasticity (Mangel 2000;West et al 2009), and the positive impact of reserves on the density-dependent survival of young fish (White 2009) which could increase the net productivity of fished populations adjacent to reserves (but see White et al 2008;Hart and Sissenwine 2009;Russ and Alcala 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As with conservation, the optimal reserve location for fisheries prosperity need not have high productivity; areas with high productive capacity can be more profitable as fished sites than as sources of spillover or export (40,42). Protecting a source population may compensate for harvest lost from the reserve area, although this potential fishery benefit certainly depends on the life history and demography of the species and will not always be realized (18,31,43).…”
Section: Locating Single Reservesmentioning
confidence: 99%
“…To benefit fisheries, the overwhelming majority of theoretical and empirical results indicate that reserve area should be divided into a network of closures whose size and spacing maximize the net effect of spillover of fishable adults and export of larvae to fished areas between the reserves (1,26,43,49,65,66). Designs characterized by a greater number of smaller reserves increase the amount of reserve edge and decrease the average distance from fished areas to the reserve edge.…”
Section: Why a Network?mentioning
confidence: 99%
See 1 more Smart Citation